Alternating current (Industrial electricity)
This seven-part CD-ROM series discusses the elements and applications of electricity that are common to any industrial facility. This series was designed in strict accordance to the current National Electrical Code. In this programme it will highlight the alternating current circuits, AC generators, inductance and capacitance, transformers and comprehensive test in the end of programme.